2011
DOI: 10.1080/00423111003602400
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid electromagnetic shock absorber for active vehicle suspension systems

Abstract: The use of electromagnetic dampers (ED) in vehicle active suspension systems has drawn considerable attention in the past few years, attributed to the fact that active suspension systems have shown superior performance in improving ride comfort and road handling of terrain vehicles, compared with their passive and semi-active counterparts. Although demonstrating superb performance, active suspensions still have some shortcomings that must be overcome. They have high energy consumption, weight, and cost and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 15 publications
1
57
0
1
Order By: Relevance
“…Kowal et al [2] developed an electro-hydraulic self-powered suspension system that accumulated energy in a pneumohydraulic accumulator. Ebrahimi et al [3,4] proposed a hybrid linear EM damper that acted as a viscous damper for ride comfort improvement, with self-powered capability. A linear motor based active suspension topology with energy regeneration capabilities was introduced by David and Bobrovsky [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kowal et al [2] developed an electro-hydraulic self-powered suspension system that accumulated energy in a pneumohydraulic accumulator. Ebrahimi et al [3,4] proposed a hybrid linear EM damper that acted as a viscous damper for ride comfort improvement, with self-powered capability. A linear motor based active suspension topology with energy regeneration capabilities was introduced by David and Bobrovsky [5].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] The so-called MR damper changes its fluid characteristics according to the magnetic field intensity. Applications of the MR damper include the seismic control of bridges and tall buildings; the suspension system for vehicles; passenger seats and washing machine drums.…”
Section: Introductionmentioning
confidence: 99%
“…The ALS has been studied analytically and tested experimentally since 1970. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The mechatronics system for theALS consists of sensors, actuators and a controller. [1] The mechatronics systems already have proven performance in tilting trains.…”
Section: Introductionmentioning
confidence: 99%
“…The external circuit was integrated to the system to observe the harvested energy properties of shock absorbers. To obtain the optimum harvesting energy from the regenerative shock absorber, the value of external resistors of system was chosen as equal to the internal resistors of the coil and generator [14], [24]- [28]. The constant resistors were used as the load of the energy harvesting system.…”
Section: Energy Harvesting Systemmentioning
confidence: 99%
“…The studies of hydraulic and EM shock absorbers have demonstrated that external electrical circuit is integrated to the system to observe the harvested energy and damping properties of shock absorbers [14], [24]- [27].…”
Section: Introductionmentioning
confidence: 99%